Bardet-Biedl syndrome: A rare genetic disease - Valverde, Diana (J Pediatr Genet, 2013)
Bardet-Biedl syndrome (BBS) is a rare multisystem genetic disease, with high phenotypic and genetic heterogeneity. Rod-cone dystrophy, obesity, polydactyly, hypogonadism, cognitive impairment and renal abnormalities have been established as primary features. There are 17 BBS genes (BBS1-BBS17) described to date, which explain 70–80% of the patients clinically diagnosed, therefore more BBS genes remain to be identified. BBS belongs to a group of diseases known as ciliopathies. In general, ciliopathies and BBS in particular share a partial overlapping phenotype that makes them complicated to diagnose. We present an up-to-date review including clinical, epidemiologic and genetic aspects of the syndrome.